Prioritizing heart transplantation during the COVID‐19 pandemic. Issue 9 (16th June 2021) - Balsara, Keki R.; Rahaman, Zakiur; Sandhaus, Emily; Hoffman, Jordan; Zalawadiya, Sandip; McMaster, William; Lindenfeld, Joann; Wigger, Mark; Absi, Tarek; Brinkley, Douglas M.; Menachem, Jonathan; Punnoose, Lynn; et al.
Abstract: Background: Coronavirus disease 2019 (COVID‐19) has significantly impacted the healthcare landscape in the United States in a variety of ways including a nation‐wide reduction in operative volume. The impact of COVID‐19 on the availability of donor organs and the impact on solid organ transplant remains unclear. We examine the impact of COVID‐19 on a single, large‐volume heart transplant program. Methods: A retrospective chart review was performed examining all adult heart transplants performed at a single institution between March 2020 and June 2020. This was compared to the same time frame in 2019. We examined incidence of primary graft dysfunction, continuous renal replacement therapy (CRRT) and 30‐day survival. Results: From March to June 2020, 43 orthotopic heart transplants were performed compared to 31 performed during 2019. Donor and recipient demographics demonstrated no differences. There was no difference in 30‐day survival. There was a statistically significant difference in incidence of postoperative CRRT (9/31 vs. 3/43; p = .01). There was a statistically significant difference in race (23 W/8B/1AA vs. 30 W/13B; p = .029). Conclusion: We demonstrate that a single, large‐volume transplant program was able to grow volume with little difference in donor variables and clinical outcomes following transplant. While multiple reasons are possible, most likely the reduction of volume at other programs allowed us to utilize organs to which we would not have previously had access. More significantly, our growth in volume was coupled with no instances of COVID‐19 infection or transmission amongst patients or staff due to an aggressive testing and surveillance program.